Rodinný dům - Klabzuba, Tomáš (Vysoké učení technické v Brně. Fakulta stavební, 2016)
Bakalářská práce se zabývá návrhem novostavby dvoupodlažního rodinného domu. Dům je obdélníkového tvaru, nepodsklepený, s plochou jednoplášťovou střechou. Objekt je konstrukčně i procesně rozdělen na obytnou a podnikatelskou část. Obytná část je navržena jako jednogenerační, pro 5 členů rodiny. Podnikatelská část slouží jako advokátní kancelář a čekárna pro klienty majitelů domu.

This bachelor thesis deals with a design of a new building of a duplex house. The house is of rectangular shape, cellarless, and with a warm flat roof. Regarding the design and procedure, the building is divided into living and business area. The living area is projected as a one-generation house for five family members. The business area serves as a lawyer’s office and a waiting room intended for the house owners’ clients.
Residential house
Keywords: Novostavba; dvoupodlažní rodinný dům; nepodsklepený; plochá jednoplášťová střecha; jednogenerační; advokátní kancelář.; New building; duplex house; cellarless; warm flat roof; one generation; lawyer’s office